2020
DOI: 10.1021/acs.est.0c04538
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Low Concentration of Graphene Oxide Increases Bacterial Pathogenicity via the Envelope Stress Response

Abstract: Graphene oxide (GO), which has diverse antimicrobial mechanisms, is a promising material to address antibiotic resistance. Considering the emergence of antibiotic tolerance/resistance due to prolonged exposure to sublethal antibiotics, it is imperative to assess the microbiological effects and related adaptive mechanisms under chronic exposure to sublethal levels of GO, which have rarely been explored. After repetitive exposure to 5 mg/L GO for 200 subcultures (400 days), evolved Escherichia coli (E. coli) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…One loach was added to a 500 mL jar containing a 250 mL 14 C-FLG suspension (50 μg/L and 250 μg/L). Notably, the concentrations of 14 C-FLG were selected based on a predicted environmental concentration of carbon nanotubes (approximately 1–1000 μg/L), because these two materials possess a number of similarities (e.g., application fields and release characteristics) and may have a similar fate. , A jar containing only freshwater was used as the control. (2) Sediment exposure: 250 mL of a 14 C-FLG suspension was slowly added into a 500 mL jar containing sediments with a depth of 4 cm, which was left to settle for 4 h, and the supernatant became clear.…”
Section: Methodsmentioning
confidence: 99%
“…One loach was added to a 500 mL jar containing a 250 mL 14 C-FLG suspension (50 μg/L and 250 μg/L). Notably, the concentrations of 14 C-FLG were selected based on a predicted environmental concentration of carbon nanotubes (approximately 1–1000 μg/L), because these two materials possess a number of similarities (e.g., application fields and release characteristics) and may have a similar fate. , A jar containing only freshwater was used as the control. (2) Sediment exposure: 250 mL of a 14 C-FLG suspension was slowly added into a 500 mL jar containing sediments with a depth of 4 cm, which was left to settle for 4 h, and the supernatant became clear.…”
Section: Methodsmentioning
confidence: 99%
“…117 Very recently, Zhang et al demonstrated that E. coli exposed to sublethal concentrations of graphene oxide over 200 passages resulted in significant alterations to both the transcriptome and the metabolic behavior through activation of an induced envelope stress response. 118 These adaptations allowed improved survival in harsh oxidative and low pH environments and facilitated greater pathogenicity through increased biofilm formation and extracellular protease release, greater bacterial invasion and intracellular survival, and greater macrophage inflammatory response. 117 This study highlights the unforeseen impact of low levels of such nanomaterials in the environment, with serious implications for human and animal health.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…Li et al [ 198 ] found that spherical and nanosheet carbon nanomaterials positively affect the upregulation of genes involved in amino acid and carbohydrate metabolism. Zhang et al studied the effect of chronic exposure to low concentrations of graphene oxide on Escherichia coli [ 199 ]. The interaction between graphene oxide and bacteria causes the significant activation of the Cpx envelope stress response, resulting in a more than two-fold increase of extracellular protease release and biofilm formation.…”
Section: Biological Effect and Applicationmentioning
confidence: 99%